Analysis of Hypertension Risk Factors among Donorers in the PMI Blood Donor - Mutia Abdullah; Asnawi Abdullah; Hermansyah Hermansyah (Indonesian Journal of Global Health Research, 2026)
Hypertension remains a global non-communicable disease problem and is a major risk factor for cardiovascular morbidity and mortality. Regular blood donation has been suggested as one strategy that may help reduce blood pressure. The Indonesian Red Cross (PMI) Blood Donor Unit in Banda Aceh City is one of the largest blood donation centers in Aceh Province, serving approximately 2,500 donors per month. This study aimed to determine the association between lifestyle, metabolic, and donation-related risk factors and the incidence of hypertension among blood donors at the PMI Blood Donor Unit in Banda Aceh City. This study employed a quantitative approach with a case–control design. Data were collected from 156 blood donors aged over 41 years who visited the PMI Blood Donor Unit in Banda Aceh City during January 12–17, 2024, consisting of 52 hypertensive donors (cases) and 104 non-hypertensive donors (controls). Participants were selected using accidental sampling. Data were obtained through donor register records and structured interviews, which included demographic characteristics, lifestyle factors, medical history, and donation frequency. Data analysis was performed using univariate analysis to describe respondent characteristics, bivariate analysis using logistic regression to assess associations between risk factors and hypertension, and multivariate logistic regression to identify the most dominant factors associated with hypertension. The results showed that employment status (OR 0.32; 95% CI; p = 0.013), poor diet (OR 11.32; 95% CI; p < 0.001), smoking status (OR 2.31; 95% CI; p = 0.018), moderate physical activity (OR 0.12; 95% CI; p < 0.001), diabetes mellitus (OR 4.11; 95% CI; p = 0.001), hypercholesterolemia (OR 4.11; 95% CI; p < 0.001), donation frequency (OR 0.71; 95% CI; p = 0.009), and body mass index (OR 1.22; 95% CI; p < 0.001) were significantly associated with the incidence of hypertension among blood donors at the PMI Blood Donor Unit in Banda Aceh City.